(untitled) (Research, Society and Development, 2022)
Objective: To verify the association between job satisfaction and common mental disorder in a sample of Brazilian Army soldiers. Method: exploratory-descriptive, cross-sectional research. With data collected through the Job Satisfaction Scale and Self Report Questionnaire 20, in a Mechanized Infantry battalion located in the state of Paraná. Result: 229 military personnel participated in the survey, in the co-workers dimension the military were very satisfied, but in the leadership, promotions and salary dimensions the participants were indifferent. The relationship between Satisfaction and Common Mental Disorder was significant (p=< 0.001) and inversely proportional (cor: -0.244). Conclusion: it is necessary to conduct institutional actions to promote mental health so that these workers continue in their careers more emotionally strengthened, expand feelings of belonging, unity among peers and the subject’s internal visibility. And, also, explore the reasons that lead them to be indifferent/apathetic about the relationship with the boss, promotions and salary.